Foraminifera and Late Cenomanian-Turonian biostratigraphy of the northern palaeobiogeographic district of Western Siberia - Podobina, Vera (Geologos, 2013)
The study of 114 core samples from seven borehole sections of the Van-Eganskaya area in the central part of Western Siberia yielded sufficient data to investigate the Late Cenomanian-Turonian foraminifers, palaeoenvironments, and the Late Cenomanian-Turonian biostratigraphy of this poorly studied area. Two Late Cenomanian foraminifer zones were established, viz. a (lower) Saccammina micra - Ammomarginulina sibirica Zone and an (upper) Trochammina wetteri tumida - Verneuilinoides kansasensis Zone. They reflect changes in the species composition of the foraminifer assemblages and lithology of the host rocks of the Uvatskian Horizon. In the lower part of the upper zone, beds with Gaudryinopsis nanushukensis elongatus are present. The changes in the species composition and lithology of the upper Cenomanian resulted from water-depth variations during the Boreal transgression. Two distinct assemblages and two homonymous zones, viz. the (lower) Gaudryinopsis angustus and the (upper) Pseudoclavulina hastata zones occur in the Turonian clayey cap-rocks of the superimposed Kuznetsovskian Horizon. Comparison of the Late Cenomanian-Turonian assemblages from the West-Siberian and Canadian provinces of the same Arctic palaeobiogeographical realm shows that the West-Siberian species are the same as, and closely related to, Canadian taxa, along with geographical subspecies. This comparison allows a detailed correlation, which results in a precise dating of the foraminifer zones.